Prevalence and Pathogenic Potentiality of Fungi Associated With Leaf Spot of Basella Alba and B. Rubra (Dhaka University Journal of Biological Sciences, 2020)
Two major species of Indian spinach, namely Basella alba L. and B. rubra L. were selected to find out associated mycoflora and their pathogenic potentiality. Ten fungi viz., Alternaria alternata, Aspergillus flavus, A. fumigatus, A. niger, Colletotrichum dematium, C. lindemuthianum, Curvularia lunata, Drechslera sacchari, Fusarium semitectum and Penicillium sp. were found to be associated with the selected leaves of Basella spp. Among the isolated fungi C. lindemuthianum, D. sacchari and F. semitectum were found to be pathogenic to Basella spp. Association of C. lindemuthianum and D. sacchari with Basella spp. are recorded first time from Bangladesh.Dhaka Univ. J. Biol. Sci. 29(2): 183-189, 2020 (July)